Innovative methods for involving people with dementia and carers in the policymaking process - Fiona Keogh; Patricia Carney; Eamon O'Shea (Wiley, 2021)
Abstract Background There are few examples of public patient involvement in policymaking for groups whose ability to participate may be affected by a disability, particularly for people with dementia and their family carers. Principles of engagement and inclusion in democratic processes are as important for these groups as other citizens. We used two innovative methods to increase involvement of people with dementia and family carers in the policymaking process in Ireland, specifically in relation to impending legislation on home care. Method A Policy Café was co‐produced with people with dementia using a World Café methodology. A Carer's Assembly was co‐produced with caregivers of people with dementia using a citizen's assembly model. Results Ten people with dementia discussed policy developments they wanted to see implemented in relation to diagnosis and home care. Twenty‐eight dementia caregivers prioritized four topics: home care; respite services; psychosocial supports; and financial supports. Film and illustrations were used to create accessible messages for policy‐makers to inform their decision making. Discussion Involving people with dementia and carers in policy development requires time and creativity to facilitate and maximize their involvement. Co‐production is essential to ensure the priorities of participants are identified, expressed and communicated effectively. A cumulative sequence of events and messages can generate significant engagement with policy‐makers. Policy‐makers need to hear the direct and authentic voice of people with dementia and carers when faced with important policy decisions. Patient or public contribution People with dementia and carers were involved in study design, data analysis and presentation.